Sanguisorba officinalis L. ethanolic extracts and essential oil – chemical composition, antioxidant potential, antibacterial activity, and ex vivo skin permeation study - Muzykiewicz-Szymańska, Anna; Nowak, Anna; Kucharska, Edyta; Cybulska, Krystyna; Klimowicz, Adam; Kucharski, Łukasz (Frontiers in Pharmacology, 2024)
The study aimed to evaluate the antioxidant activity and total polyphenol content (TPC) of extracts prepared in 70% and 40% aqueous ethanol solution (dry extract content 50-500 g/L) from the aerial parts of S. officinalis. The essential oil was isolated from the tested raw material, and its composition was determined using GC-MS. Extracts prepared in ethanol at 70% and 40% v/v (dry extract content 50-500 g/L) and essential oil have been tested for antibacterial activity. The extract in 70% v/v ethanol (dry extract content: 500 g/L) was subjected to HPLC analysis for the content of selected phenolic acids and an ex vivo skin permeation study. The ability of these metabolites to permeate and accumulate in the skin was analysed. Extracts prepared at both ethanol concentrations showed similar antioxidant activity and TPC. Depending on the method, concentration of solvent, and dry extract content (50-500 g/L), the activity ranged from 1.97 to 84.54 g Trolox/L. TPC range of 3.80-37.04 g GA/L. Gallic acid (424 mg/L) and vanillic acid (270 mg/L) had the highest concentrations among the phenolic acids analysed. Vanillic acid (10 μg) permeates the skin at the highest concentration. The highest accumulation in the skin was found for 2,5-dihydroxybenzoic acid (53 μg/g skin), 2,3dihydroxybenzoic acid (45 μg/g skin), and gallic acid (45 μg/g skin). The tested ethanolic extracts exhibited antibacterial activity. Samples with a dry extract concentration of 500 g/L showed the largest growth inhibition zones. The most sensitive strains to these extracts were P. aeruginosa (24 mm), S. lutea (23 mm), and S. pneumoniae (22 mm). The smallest inhibition zones were observed for B. subtilis (17 mm). The essential oil showed weaker antimicrobial activity (growth inhibition zone 8-10 mm). The GC-MS method identified 22 major components of the essential oil, including aliphatic hydrocarbons, unsaturated terpene alcohols, aliphatic aldehydes, unsaturated and saturated fatty acids, sesquiterpene, phytyl ester of linoleic acid, nitrogen compound, phytosterol, terpene ketone, phenylpropanoids, aliphatic alcohol, diterpenoid, aromatic aldehyde, and aliphatic carboxylic acid.